Comparative analysis of the aberrant immunophenotype and clinical characteristics in dogs with lymphoma: a study of 27 cases - Bae, Hyeona; Kim, Sang-Ki; Yu, DoHyeon (Frontiers in Veterinary Science, 2023)
Introduction: Aberrant lymphoma phenotypes are frequently found in dogs, but the clinical implications are sparse.Methods: Twenty-seven dogs with aberrant lymphoma diagnosed using flow cytometry between 2017 and 2023 were analyzed. Major paraneoplastic syndromes, prognostic factors, and clinical features of lymphoma were compared to their immunophenotypes.Results: Twenty-seven dogs had aberrant immunophenotypes, with MHCII-(48%) and CD3+/CD21+ (44%) being the most commonly identified aberrancies. In B-cell lymphoma, the most frequent aberrancies were MHC II-(53%), CD3+/CD21+ (41%), CD34+ (24%), and CD79a-(24%). Meanwhile, in T-cell lymphoma, CD3+/CD21+ (63%), CD4-/CD8-(50%), CD5-(50%), and CD45-(50%) were the most common. The platelet-neutrophil ratio was significantly higher in the CD3+/CD21+ group than in the other groups, where either one or both markers were not expressed (55. 23 ± 39.64; 18.72 ± 14.95, respectively; P=0.001). Serum albumin concentration was significantly lower in the MHCII-group (2.59 g/dL, 95% CI 2.31-2.87) than in the MHCII+ group (3.06 g/dL, 95% CI 2.88-3.23; P=0.009). CD34 expression showed significant correlations with cranial mediastinal mass, WHO clinical substage, and fever (P=0.028, P=0.041, and P=0.047, respectively). MHCII expression was correlated with adverse reactions to chemotherapy, cranial mediastinal masses, and fever (P=0.009, P=0.023, and P<0.001, respectively). No statistically significant differences in the survival period were observed for any of the phenotypic aberrancies.Aberrant lymphomas are common in dogs. Some clinical prognostic factors that significantly correlate with aberrant immunophenotypes have been identified and can be applied clinically.